Aplikasi Pencatatan Data Dasar (PEDDAS) pada Pembinaan Kesejahteraan Keluarga Berbasis Website di Kelurahan Tamanbaru Banyuwangi - Djuniharto Djun; Rudi Hartono Rudi (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Family Prosperity Founding is an institution that is very closely related to the system ofgovernment and society. Various types of community data in an environment must bemanaged by the Family Prosperity Founding, both at the village / kelurahan and district levels.In managing community data, many parties are involved, from the managers of each of theguest houses for each RT to the Village / Village Office. Of course this requires a lot of energyand time so that it is not fast in presenting information needed by certain parties. What is donefor data collection on the Family Prosperity Founding of a village / kelurahan has thefollowing stages: 1. The initial data is made by each charisma in each RT, 2. RT records thedata obtained from the dasawisma group and then the data is given to RW, 3. RW receivesdata from each RT and recapitulation, then the RW provides data to the Working Group, 4.The working group recaps data from the assisted RW and provides recapitulation data to thevillage / kelurahan, 5. The village / kelurahan reconciles the overall data. This method tendsto cause errors in filling and the slow submission of data to the kelurahan. For this reason, awebsite-based PEDDAS application was created in the hope that it could overcome problemsand be able to present Family Prosperity Founding information in Tamanbaru Village. Theconclusion of this reserach is the basic data registration application on Family ProsperityFounding facilitates the Dasa Wisma group to input group’s data and activities on 10 mainprograms of the Family Prosperity Founding at Tamanbaru Banyuwangi Urban Village. Thisapplication is also able to give information about all Family Prosperity Founding activitiesdone by its members to the Family Prosperity Founding board in Urban Village Office